La "Aufklärung" en la onología del presente de Michel Foucault - Torrano, Andrea (Nómadas. Critical Journal of Social and Juridical Science, 2011)
In this article I propose to inquire the Aufklärung concept developed by Michel Foucault, and leads him to inclusion in the “critical tradition” initiate by Immanuel Kant. I consider that the nearness between Foucault and Kant –observed in the lasts courses and writings- is mainly due to the Foucault’s distinction between two traditions founded by Kant: an “analytics of truth” and an “ontology of the present”. The conception of Aufklärung as a critique, in its triple aspects: governmentality, present and ethos, makes it possible that Foucault advocates by ontology of the present, but without taking the full Kantian project.
Keywords: Aufklärung; critic; ontology of the present; Foucault; Kant